Effect of Muscle Energy Technique as an Adjunct to Lumbar Stabilisation Exercise Training on Pain, Disability and Fear Avoidance belief in Patients with Chronic Low back pain with facet joint dysfunction: Randomized Controlled Trial - Shubhangi Patil; Muskan Bhojwani (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Low back pain (LBP) is the second leading cause of disability, affecting 85 percent of peopleworldwide at some point in their life. LBP is viewed as a personal and societal burden due to discomfort andlimited function. Facet joint dysfunction is one of the leading causes of pain and disability. While the MuscleEnergy technique (MET) looks to be a promising treatment, research on MET in combination with exercise therapyis limited.Method: Sixty patients, 18 to 40 years of age, with a history of chronic low back pain will be randomly divided intotwo groups. One group will receive lumbar stabilization exercise training along with muscle energy techniqueand the other group will receive lumbar stabilization exercise training alone respectively for 3 times a weekfor 4 weeks. Data will be collected pre and post the intervention on the Numeric Rating Scale, Oswestry LBPDisability Questionnaire, and Fear-avoidance belief questionnaire.Result: Both groups will be analyzed for pain, disability, and patients’ fear-avoidance belief regarding physicalactivity Baseline characteristics including means and standard deviations (SDs) will be analyzed. Categoricalvariables will be analyzed with a chi-square test and continuous variables will be analyzed using independentt-tests.